ANALISIS PENGARUH KUALITAS LAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN UNTUK MENCIPTAKAN LOYALITAS KONSUMEN (Studi Kasus pada Konsumen Salwa House Kafe di Tembalang) - Rofa, Milzam Haidi; Dwiyanto, Bambang Munas (Diponegoro Journal of Management, 2016)
This study aimed to analyze the effects arising from the Service Quality and Store Atmosphere on Consumer Satisfaction and its influence on Consumer Loyalty from consumer of Salwa House cafe. The variables used in this study is Service Quality and Store Atmosphere as an independent variable, then the Consumer Satisfaction as an intervening variable and Consumer Loyalty as the dependent variable.The samples in this study is consumers of Salwa House cafe with some 104 people by using Non-Probability Sampling techniques. In this study developed a theoretical model to propose three hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 21.0. Based on the research of data processing SEM for full model has met the criteria of goodness of fit as follows, the value of chi-square = 66,232; probability = 0,062; RMSEA = 0,056; CMIN/DF = 1,325; GFI = 0,913; TLI = 0,980; CFI = 0,985; NFI = 0,941; and a marginal criteria which is AGFI = 0,864.With the result of goodness of fit criteria that it can be said this model is feasible to be used. The result of sem analysis showed that the variable of Service Quality and Store Atmosphere had positive influences on Consumer Satisfaction with an equation KK=0.405KL + 0.472SA + z1. And Consumer Satisfaction had positive influences on Consumer Loyalty with an equation LK = 0.847KK + z2. And than the results of hypothesis testing showed that the Customer Loyalty can be improved by increasing Service Quality and Store Atmosphere affect the Customer Satisfaction as a determinant of success increase Customer Loyalty.